Phytochemical Profiling and Pharmacological Evaluation of Ethanolic Extract of Moringa oleifera Leaves Loaded in Solid Lipid Nanoparticles for Antidiabetic Activity - Johnson, Benito; Jahnavi, Patibandla; Nehere, Shital Vijay; Thakur, Diksha; Monika, Monika; Tawale, Hemant; Singh, Birender; Parvez, Nayyar (Journal of Neonatal Surgery, 2025)
Introduction: Moringa oleifera leaves contain a wealth of bioactive chemicals that have been shown to have therapeutic effects, particularly in the management of diabetes. Their low bioavailability and poor water solubility, however, restrict their practical usefulness. This study intends to improve the antidiabetic effectiveness of Moringa oleifera ethanolic extract by combining it with solid lipid nanoparticles. Then, it will conduct phytochemical profiling and pharmacological evaluation in diabetic rats induced by streptozotocin. Materials and Methods: Moringa oleifera leaves were macerated in 70% ethanol to produce an ethanolic extract. utilizing stearic acid as the lipid and Poloxamer 188 as the surfactant, solid lipid nanoparticles (MOEE-SLNs) were synthesized utilizing the hot homogenization followed by ultrasonication method. There was confirmation of the presence of quercetin, kaempferol, chlorogenic acid, and β-sitosterol through phytochemical screening using HPTLC and GC-MS. The size of the particle and its zeta potential were measured using DLS and were reported to be 145.8 ± 3.5 nm and -28.6 ± 1.2 mV, similarly. The estimated entrapment efficiency was 82.4 ± 2.1%. Research on the release of drugs in vitro at a pH of 7.4 showed a steady release pattern lasting up to 24 hours, with a release rate of 87.5 ± 3.8%. Six diabetic Wistar rats produced with streptozotocin were used to study the antidiabetic effect in vivo. They checked the subjects' blood glucose levels at0,7,14, and 21 days. Results: In comparison to the simple MOEE group, which lowered fasting blood glucose to 167.4 ± 7.8 mg/dL after 21 days (p < 0.001), the MOEE-SLN-treated group (100 mg/kg) demonstrated a notable decrease, going from 282.6 ± 9.4 mg/dL to 118.3 ± 6.1 mg/dL. The histopathological analysis of pancreatic tissues showed that the MOEE-SLN group had better β-cell regeneration than the diabetic control group. Compared to plain extract, MOEE-SLN increased glucose clearance by 45.2% in the oral glucose tolerance test (OGTT). Insulin levels, total cholesterol, triglycerides, and hemoglobin A1c were all markedly improved in the MOEE-SLN group. Conclusion: The antidiabetic action of Moringa oleifera ethanolic extract is much improved when it is encapsulated into solid lipid nanoparticles. This is because it improves bioavailability, provides sustained release, and protects pancreatic β- cells. In light of these results, MOEE-SLNs may be useful as a natural nanotherapeutic in the treatment of diabetes